Development of a miniaturized electrochemical biochip - Bella, Giovanni; Calorenni, Paolo; Yadav, Neeraj; Sciuto, Emanuele Luigi; Messina, Angelo Alberto; Buonasera, Katia; Lorenzelli, Leandro; Conoci, Sabrina (Frontiers in Lab on a Chip Technologies, 2025)
The technological evolution towards portable systems for nucleic acids (NAs) analysis is central in diagnostics and healthcare. Conventional approaches for genetic analysis require multistep procedures, from the genetic material purification to its detection, that are mostly based on the NA amplification by polymerase chain reaction (PCR) and constrained to bulky specialized instruments and dedicated laboratories. These limitations imply an increase in time and cost of analysis avoiding the possibility of massive molecular screening, as in the case of an infectious pandemic, and accessible diagnosis. Therefore, research efforts are moving towards new Lab-on-a-chip (LoC) technologies that guarantee a more integrated, decentralized, user-friendly, and low-cost NA analysis. These are based on miniaturized optical or electrical chips on which it is possible to integrate a sensing surface for specific analytical applications. In this scenario, we presented the fabrication and characterization of a miniaturized electrochemical (EC) biochip as a potential LoC for genetic applications. The chip was developed with microfabricated electrodes on top and polycarbonate/PDMS microchambers for the surface treatment and functionalization. The characterization of chip EC performances has been performed by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). Moreover, the chip surface has been functionalized with thiol-modified oligonucleotides, whose immobilization has been characterized by contact angle (CA) and surface free energy (SFE) analysis. Results reported a good robustness and responsivity of the chip proving its suitability for sensing array preparation and integration in a LoC format.